Circulating Lipids and Acute Pain Sensitization: An Exploratory Analysis. Issue 6 (November 2017) - Starkweather, Angela; Julian, Thomas; Ramesh, Divya; Heineman, Amy; Sturgill, Jamie; Dorsey, Susan G.; Lyon, Debra E.; Wijesinghe, Dayanjan Shanaka
Abstract : Background: In individuals with low back pain, higher lipid levels have been documented and were associated with increased risk for chronic low back pain. Objectives: The purpose of this research was to identify plasma lipids that discriminate participants with acute low back pain with or without pain sensitization as measured by quantitative sensory testing. Methods: This exploratory study was conducted as part of a larger parent randomized controlled trial. A cluster analysis of 30 participants with acute low back pain revealed two clusters: one with signs of peripheral and central sensitivity to mechanical and thermal stimuli and the other with an absence of peripheral and central sensitivity. Lipid levels were extracted from plasma and measured using mass spectroscopy. Results: Triacylglycerol 50:2 was significantly higher in participants with peripheral and central sensitization compared to the nonsensitized cluster. The nonsensitized cluster had significantly higher levels of phosphoglyceride 34:2, plasmenyl phosphocholine 38:1, and phosphatidic acid 28:1 compared to participants with peripheral and central sensitization. Linear discriminant function analysis was conducted using the four statistically significant lipids to test their predictive power to classify those in the sensitization and no-sensitization clusters; the four lipids accurately predicted cluster classification 58% of the time ( R 2 = .58, −2 log likelihood = 14.59). Discussion: The results of this exploratory study suggest a unique lipidomic signature in plasma of patients with acute low back pain based on the presence or absence of pain sensitization. Future work to replicate these preliminary findings is underway.